Comparison of Vegetable Oils and Monitoring of Rancidity and Lard Adulteration in Palm Olein Using Electronic Nose - Gan, Howe Lin (2004)
Flavour analysis is typically performed by organoleptic panel, which is often expensive and less objective. A novel approach using a surface acoustic wave (SAW) sensing-based electronic nose (zNose™) for flavour analysis was explored in this study for determination of some parameters of edible oils and fats.